Asymmetric Access to Chiral Sulfinyl Compounds as Bioisosteres of Carbonyl Compounds - Wang, Chenxin; Wu, Xinyu; Huang, Jiapian; Liu, Gang; Wu, Jie (Synthesis, 2024)
The sulfinyl group, as one of the bioisosteres of carbonyl groups, attracts considerable attention in the field of synthetic chemistry. In particular, the asymmetric construction of chiral sulfinyl compounds and their derivatives remains in the early stages of development. Sulfinyl compounds mainly include sulfoxides, sulfinate esters and sulfinamides, according to the different functional groups connected to the sulfur atom. This Review summarizes the fascinating recent progress made over the past decade on the asymmetric synthesis of enantiopure sulfinyl derivatives.1 Introduction2 Asymmetric Synthesis of Chiral Sulfoxides3 Asymmetric Synthesis of Chiral Sulfinate Esters4 Asymmetric Synthesis of Chiral Sulfinamides5 Conclusion and Outlook
Keywords: sulfinyl; bioisostere; asymmetric synthesis; sulfoxide; sulfinate ester; sulfinamide